2015
DOI: 10.1002/jbio.201400131
|View full text |Cite
|
Sign up to set email alerts
|

GJIC Enhances the phototoxicity of photofrin‐mediated photodynamic treatment by the mechanisms related with ROS and Calcium pathways

Abstract: Despite initially positive responses, recurrences after Photodynamic treatment (PDT) can occur and there is need for improvement in the effectiveness of PDT. Our study uniquely showed that there was a significantly gap junctional intercellular communication (GJIC)-dependent PDT cytotoxicity. The presence of GJIC composed of Connexin 32 increased the PDT phototoxicity in transfected HeLa cells and in the xenograft tumors, and the enhanced phototoxicity of Photofrin-mediated PDT by GJIC was related with ROS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 44 publications
0
22
2
Order By: Relevance
“…Besides the above‐mentioned representative work, the research interests of China researchers are quite diverse, covering technique development through to biomedical applications. Consulting the papers published over the last three years in Journal of Biophotonics, the hot topics include photoacoustic microscopy , other technical improvement for imaging , photodynamic therapy , and human studies .…”
Section: Research Interests Indicated By Jbpmentioning
confidence: 99%
“…Besides the above‐mentioned representative work, the research interests of China researchers are quite diverse, covering technique development through to biomedical applications. Consulting the papers published over the last three years in Journal of Biophotonics, the hot topics include photoacoustic microscopy , other technical improvement for imaging , photodynamic therapy , and human studies .…”
Section: Research Interests Indicated By Jbpmentioning
confidence: 99%
“…Photofrin‐mediated PDT has firstly been approved in 1993 in Canada for the prophylactic treatment of bladder cancer . Our previous studies showed that homotypic Cx32‐ and Cx26‐composed GJIC‐mediated “bystander effect” could enhance the phototoxicity of Photofrin‐mediated PDT . The present study represented the first demonstration of the ability of heterotypic Cx32/Cx26‐composed GJIC to have a “Good Samaritan” effect on HeLa cells following Photofrin‐PDT treatment.…”
Section: Introductionmentioning
confidence: 50%
“…The Western blot assay was utilized as described in our previous studies . Briefly, after protein samples were separated, samples were transferred to nitrocellulose transfer membrane (Excell Bio, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to isolate PDT agents inside drug delivery vehicles because these highly sensitive species could become toxic with exposure to even ambient levels of light. 177 Nevertheless, due to the high level of similarity between PDT and PTT, it made sense to design systems with both modes of therapy integrated. Jang et al demonstrated an interesting example by using AuNRs as both carrier and quencher for the PDT agent, aluminum phthalocyanine tetrasulfonate (AlPcS 4 ).…”
Section: Combination Phototherapiesmentioning
confidence: 99%